THE VIOLATION OF COOPERATIVE PRINCIPLE A CASE OF HUMOROUS VERBAL CARTOON IN KOMPAS - Mory Yana Gultom; Elia Masa Gintings (State University of Medan, 2013)
Abstract This research is aimed at describing the types of maxim violated in humorous verbal cartoon in Kompas, to find out the type of the maxims that is dominantly violated in it and to find out the causes. The method of research is descriptive qualitative research. The data is analyzed by interpreting the conversations and analyzing them based on the types of the maxim violated. From the data, it was found that the violation of the maxim of quality is 12 (20.33%), the violation of the maxim of quantity is 25 (42.37%), the violation of manner is 15 (25.42%), and the violation of the maxim of relevance is 7 (11.86%). The frequency and the percentage shows that maxim of quantity is the dominant type of maxim which is violated. Key words: cooperative principle, maxim, cartoon, humor